Analysis of Instrument Development to Measure The Pancasila Student Profile Using The Rasch Model - Novalia, Melly; Asma Lailee,; Vitriani, (Journal of Social Transformation and Regional Development, 2025)
This study aims to analyze the validity and reliability of the instrument for forming Pancasila student profiles using the Rasch Model. The Rasch model is a method that has the advantage of being able to provide more accurate estimates and at the same time being able to detect model inaccuracies. This research is a type of quantitative research with a survey method. The research subjects were 100 high school level Islamic boarding school students. To analyze the data, the Winstep application version 9.0.3.0 was used using the Rasch Model method. The results of the study obtained a Cronbach Alpha reliability value of 0.93 which means that the reliability of the instrument was categorized as very good, for the quality of the statement items on the Pancasila student profile instrument it was worth 0.97 in the special category, the reliability or consistency of answers from respondents got a value of 0.92 in the very good category. Based on these results, the instrument for forming Pancasila student profiles can be used by educators to assess students' attitudes based on Pancasila student profiles and can also be used by educators outside Islamic boarding schools with similar assessment needs.